Spatial price analysis of tomatoes in nigeria (2012)
The study examined market integration in tomato markets in selected producing and consuming states in Nigeria. Secondary data on tomato prices spanning 2003 -2006 were sourced from National Bureau of Statistics. The data were analyzed using Augmented Dicker Fuller (ADF) and Granger Causality tests. Results indicated that the maximum tomato price was recorded in Ekiti in November, 2006 while the minimum price was recorded in Kano state in August, 2006. The results also revealed that prices of tomato were not stationary in their level form but become stationary at the first difference lever Seven tomato markets rejected their respective null hypothesis of no granger causality. None of the markets exhibited bi -directional granger causality or simultaneous feedback relationships Seven markets exhibited unidirectional granger causality. The results also indicated that Ekiti and Katsina states occupy the leadership position in tomato price formation and transmission. We recommend there should be efficient flow of information and good access road and infrastructural development among the states to improve market performance.